Sesquiterpene Lactones and Penta Methoxylated Flavone from Artemisia kulbadica - Rustaiyan, Abdolhossein; Ezzatzadeh, Elham (Asian Journal of Chemistry, 2010)
The aerial parts of Artemisia kulbadica afforded a germacranolide and a guaianolide type sesquiterpene lactones together with a pentamethoxylated flavone. The structures were elucidated by spectropic methods, including 1D and 2D NMR analysis.